Antibacterial Activity Test of Tembelekan Leaf Extract (Lantana camara linn) against Edwardsiella tarda bacteria - Marwulan Marwulan; Happy Nursyam; Yuni Kilawati (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to analyze the optimal dose of Tembelekan leaf extract (Lantana camara Linn) which has antibacterial properties in inhibiting or killing Edwardsiella tarda bacteria. The method used in this research is Completely Randomized Design (CRD). The results of the research yield obtained from tembelakan leaf extract amounted to 8.9%. The positive phytochemical test results contained active compounds, namely flavonoids, alkaloids, tannins, triterpenoids, and saponins. GC MS analysis of tembelekan leaf extract showed that the most components were 4H-1-Benzopyran-4-one, 5,7-dihydroxy-6-methoxy-2-(4-methoxyphenyl)-,2,1,3-Benzothiadiazole, Benzisot hiadiazole , 3,4-Benzo-1,2,5-thia diazole. This compound is a class of isoflavonoids compounds. The MIC (Minimum Inhibitory Concentration) test results obtained the lowest absorbance value at a concentration of 100 mg/L with a value of 0.602 close to the positive control. Results of discs with doses of 50, 100, 150, 200, and 250 mg/L. The disc results showed that the dose of 200 mg/L had the strongest inhibition zone with a value of 12.63 mm. Tembelekan leaf extract which contains dominant compounds such as flavonoids and alkaloids can be useful as an antibacterial which inhibits the growth of E. tarda bacteria